Sistem Informasi Distribusi PAMDES pada Desa Saragih Berbasis Website dengan Metode Waterfall: Website-Based PAMDES Distribution Information System in Saragih Village using the Waterfall Method - Sihotang, Noel; Matondang, Zekson Arizona; Tampubolon, Kennedi (KAKIFIKOM : Kumpulan Artikel Karya Ilmiah Fakultas Ilmu Komputer, 2023)
The distribution of Pamdes in Saragih village is still done manually. To register to become a member, residents need to find the officer directly and for payment the officer must directly bill the user. To solve this problem, a Pamdes information system design was created which handles registration and payments for Pamdes users. In designing this Pamdes information system, the author uses the Waterfall model. It is hoped that the results of designing this information system will make it easier for the public to register and register as well as assist officers in processing data in the Pamdes.